(untitled) (Scientific journal of the Fergana State University, 2023)
In the course of this study, a starch unit was introduced into the chain of a copolymer consisting of polyethylene and polyacrylonitrile. The biodegradability and thermal stability of the composition is improved by introducing starch into the copolymer chain. Also, in the course of the research, IR spectroscopic and derivatographic indicators of the composition of the composition of polyethylene, polyacrylonitrile and starch were studied and analyzed. According to the results of scientific research, the best heat resistance of the polyethylene-polyacrylonitrile-starch composition in relation to polyethylene has been proven.